Planejamento de obras residenciais não repetitivas com construção enxuta e BIM - Lima, Fernanda Martignago de (2023)
Over the last two decades, researchers have been evaluating the application of Lean Construction (Lean Construction) and the Building Information Model – BIM (Information Modeling in Construction). Information Modeling in Construction allows, through 4D BIM models, the visualization of the construction process in real time. Despite advances on the topic, it is important to evaluate the implementation process of these technologies with concepts that can contribute to the analysis of processes, through Business Process Management – BPM (Business Process Management). Taking into account the characteristics that generate uncertainty in the sector's production process, the purpose of this work was to evaluate the results of innovation in processes with the implementation of Lean Construction for long-term planning in non-repetitive residential works with the support of BIM and BPM. The following were listed in the research methodology: modeling requirements, executive sequence, team synchronization, schedule development, standardization of work packages, and quality of information and communication of those involved. Problems relating to the construction sequence were identified through the visualization of each activity to be carried out in the package, as well as necessary assumptions for planning when integrating BIM models with the schedule work packages. Improvements were proposed through the presentation of modeling requirements, highlighting: creation of shared parameters; compatibility of discipline coordinates; choice of BIM object modeling methods; and, checking the absence of BIM objects.